2013
DOI: 10.1089/cell.2012.0055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Donor Fibroblasts Expressing OCT4 on Bovine Embryos Generated by Somatic Cell Nuclear Transfer

Abstract: The production of healthy, live, cloned animals by somatic cell nuclear transfer (SCNT) has been hampered by low efficiencies. Significant epigenetic changes must take place to ensure proper chromatin remodeling in SCNT. We hypothesized that exogenous expression of OCT4 in donor fibroblasts prior to its fusion with enucleated oocytes would facilitate SCNT reprogramming. We infected bovine adult fibroblasts with retroviral vectors containing yellow fluorescent protein (YFP) only, or the OCT4 gene fused to YFP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…For example, the implantation of blastocysts and maintenance of pregnancy require the silencing of OCT4 in the trophectoderm (Liu et al, ), which is prerequisite for the expression of CDX2 . Yet, an increase in CDX2 expression in SCNT embryos reconstructed with OCT4 ‐overexpressing donor fibroblasts in bovine was reported (Goissis et al, ), and we observed a significant elevation in CDX2 expression in OCT4 ‐SCNT blastocysts (Fig. F).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…For example, the implantation of blastocysts and maintenance of pregnancy require the silencing of OCT4 in the trophectoderm (Liu et al, ), which is prerequisite for the expression of CDX2 . Yet, an increase in CDX2 expression in SCNT embryos reconstructed with OCT4 ‐overexpressing donor fibroblasts in bovine was reported (Goissis et al, ), and we observed a significant elevation in CDX2 expression in OCT4 ‐SCNT blastocysts (Fig. F).…”
Section: Discussionsupporting
confidence: 69%
“…Notably, the overexpression of exogenous OCT4 was transient in both studies, meaning that exogenous OCT4 is only necessary at initial stages of development. On the other hand, Goissis et al () reported no difference in the development rate when fibroblasts expressing OCT4 were used as donor cells in bovine SCNT. Further, ectopic expression of OCT4 can cause dysplasia in epithelial tissues in adult mice (Hochedlinger et al, ), suggesting that constant overexpression of OCT4 could interfere with normal development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between the regulation of pluripotency genes and DNA methylation is critical for early embryonic development (Goissis, Suhr, & Cibelli, ; Hattori et al, ). Previous studies have found that the pluripotency genes SOX2 and CDX2 are at a low methylation level at all stages of porcine IVF embryo development (Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence staining analysis of 5mC to 5hmC is crucial for the study of DNA demethylation dynamics during early embryonic development. Previous studies have found that during The interaction between the regulation of pluripotency genes and DNA methylation is critical for early embryonic development (Goissis, Suhr, & Cibelli, 2013;Hattori et al, 2007). Previous studies have found that the pluripotency genes SOX2 and CDX2 are at a low methylation level at all stages of porcine IVF embryo development .…”
Section: Discussionmentioning
confidence: 99%